2014
DOI: 10.1002/stem.1545
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensitivity to JAK Inhibitory Drugs by Isogenic Human Erythroblasts and Hematopoietic Progenitors Generated from Patient-Specific Induced Pluripotent Stem Cells

Abstract: Disease-specific induced pluripotent stem cells (iPSCs) provide an unprecedented opportunity to establish novel disease models and accelerate drug development using distinct tissue target cells generated from isogenic iPSC lines with and without disease-causing mutations. To realize the potential of iPSCs in modeling acquired diseases which are usually heterogeneous, we have generated multiple iPSC lines including two lines that are JAK2-wild-type and four lines homozygous for JAK2-V617F somatic mutation from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 52 publications
3
52
3
1
Order By: Relevance
“…The successful reprogramming of erythroid progenitors derived from patients with polycythemia vera has been described recently. 44 In a recent study our iPSC derived from mouse NSC with OCT4 alone showed reduced neuronal and hematoendothelial differentiation compared to iPSC reprogrammed with all four factors or ESC. 45 This might be the result of some epigenetic instability, as shown in the DNA methylation pattern of the pluripotency associated promoters, although their gene expression profile was very similar to that of ESC.…”
Section: Discussionmentioning
confidence: 91%
“…The successful reprogramming of erythroid progenitors derived from patients with polycythemia vera has been described recently. 44 In a recent study our iPSC derived from mouse NSC with OCT4 alone showed reduced neuronal and hematoendothelial differentiation compared to iPSC reprogrammed with all four factors or ESC. 45 This might be the result of some epigenetic instability, as shown in the DNA methylation pattern of the pluripotency associated promoters, although their gene expression profile was very similar to that of ESC.…”
Section: Discussionmentioning
confidence: 91%
“…For this purpose, we again chose to target the somatic JAK2-V617F (rs77375493, G>T) mutation and the inherited α1-antitrypsin (AAT) Z mutation (rs28929474, G>A) in the SERPINA1 gene. Two panels of healthy donor and patient-derived iPSCs carrying either a homozygous wild-type target allele, heterozygous mutant allele or homozygous mutant allele were used in these experiments [26,28,[32][33][34] (Table 1). Two gRNAs, gRNA-JAK2-F and gRNA-JAK2-V, were designed with a single nucleotide difference to specifically recognize the V617F mutant allele (T) or the wild-type allele (G) of JAK2 (Fig 4a).…”
Section: Homologous Donorsmentioning
confidence: 99%
“…1). Normal iPSCs that genetically match the malignant iPSCs can be derived from the same cancer patients to provide paired tumor and normal iPSCs that share the same genetic background 29,31,33 . These can be derived in parallel, through the same reprogramming experiment from normal cells that frequently ‘contaminate’ a tumor specimen, and identified retrospectively through genetic analyses 29,31 .…”
Section: Ipscs and Cancer Modelingmentioning
confidence: 99%